Magnetic study of paramagnetic compounds M(AsF6)2 (M = Co, Mn) and Co(AsF6)2.2L (L = AsF3, SbF3, SO2) - Jagličić, Zvonko (Acta chimica slovenica, 2002)
DC magnetization measurements with a SQUID susceptometer have been performed on ?$Mn(AsF_6)_2$? ?$Co(AsF_6)_2$? and three ?$Co(AsF_6)_2$? compounds with different ligands ?$(AsF_3, SbF_3, SO_2$?. All samples demonstrate paramagnetic behaviour above 50 K. The measured Curie constants are compatible with ?$Mn^{+2}$? and ?$Co^{+2}$? ions. An addition, the samples with ?$Co$? atoms show magnetic ordering below 40 K. Investigation of arsenic NQR only in ?$Co(AsF_6)_2 · 2AsF_3$?, reveals three lines: one near 122 MHz and two near 50 MHz. Relation of these spectral lines to the structure is obtained. Possible influence of paramagnetic ?$Co$? is examined.
Keywords: fluoridi; kobaltove spojine; magnetne lastnosti; manganove spojine